2021
DOI: 10.1002/eat.23517
|View full text |Cite
|
Sign up to set email alerts
|

Food insecurity associated with elevated eating disorder symptoms, impairment, and eating disorder diagnoses in an American University student sample before and during the beginning of the COVID‐19 pandemic

Abstract: Objective This study tested the association between food insecurity and eating disorder (ED) pathology, including probable ED diagnosis, among two cohorts of university students before and during the beginning of the COVID‐19 pandemic. Method Students (n = 579) from a large Midwestern American university completed self‐report questionnaires assessing frequency of ED behaviors, ED‐related impairment, and individual food insecurity as measured by the Eating Disorder Diagnostic Scale 5, Clinical Impairment Assess… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
61
0
2

Year Published

2021
2021
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 59 publications
(75 citation statements)
references
References 42 publications
2
61
0
2
Order By: Relevance
“…University students may have modified or stopped their paid activity [15] which could have led to food insecurity [16]. In the United States, studies showed that university students with food insecurity were more likely to screen positive for an ED [17], especially during the COVID-19 pandemic [18]. The COVID-19 pandemic has also led to anxiety and depression symptoms among university students [19,20] which are well known to be associated with ED [21,22].…”
Section: Introductionmentioning
confidence: 99%
“…University students may have modified or stopped their paid activity [15] which could have led to food insecurity [16]. In the United States, studies showed that university students with food insecurity were more likely to screen positive for an ED [17], especially during the COVID-19 pandemic [18]. The COVID-19 pandemic has also led to anxiety and depression symptoms among university students [19,20] which are well known to be associated with ED [21,22].…”
Section: Introductionmentioning
confidence: 99%
“…College students are a vulnerable group in relation to their nutritional health, owing to changes in lifestyle and the production in young students of food insecurity and changes in body weight and composition [ 10 , 20 , 27 ].…”
Section: Discussionmentioning
confidence: 99%
“…Another notable change in the lives of the students will be the coexistence with other students who arrive at the university in this period 2020/21; In these cases, living without a family environment in a university environment may cause alterations in eating habits and facilitate the appearance of eating disorders. It's more, a post-pandemic experience of confinement, social distancing and the perception of the risk for their health due to COVID-19, can favor this type of pathology [ 19 , 20 , 36 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…A vulnerabilidade e a insegurança alimentar são fatores amplamente identificados entre estudantes. A escassez de recursos financeiros, excesso de atividades e gastos acadêmicos, são condições que contribuem significativamente para o desenvolvimento de diversos desequilíbrios nutricionais (Christensen et al, 2021).…”
Section: Discussionunclassified